Effects of Adjuvants on the Safety and Immunogenicity of an Avian Influenza H5N1 Vaccine in Adults - Bernstein, David I.; Edwards, Kathryn M.; Dekker, Cornelia L.; Belshe, Robert; Talbot, Helen K. B.; Graham, Irene L.; Noah, Diana L.; He, Fenhua; Hill, Heather (The Journal of infectious diseases, 2008)
Background. Influenza A H5N1 viruses pose a significant threat to human health. Methods. We conducted a multicenter, randomized, double-blind study in 394 healthy adults. Subjects were randomly assigned to receive 2 intramuscular doses of either saline placebo; influenza A/Vietnam/1203/2004(H5N1) vaccine alone at 45, 30, or 15 µg per dose; vaccine at 15 or 7.5 µg per dose with MF59; or vaccine at 30, 15, or 7.5 µg per dose with aluminum hydroxide. Subjects were followed up for safety and blood samples were obtained to determine antibody responses. Results. The vaccine formulations were well tolerated but local adverse effects were common; the incidence of these effects increased in a dose-dependent manner and was increased by the addition of adjuvants. The addition of MF59 increased the antibody response, whereas the addition of aluminum hydroxide did not. The highest antibody responses were seen in the group that received 15 µg of vaccine per dose with MF59, in which 63% of subjects achieved the predetermined endpoint (hemagglutination-inhibition titer ⩾40) 28 days after the second dose, compared with 29% in the group that received the highest dose (45 µg per dose) of vaccine alone. Conclusions. A 2-dose regimen of subvirion influenza A (H5N1) vaccine was well tolerated. The antibody responses to 15 µg of A/H5 vaccine with MF59 were higher than the responses to 45 µg of vaccine alone. Trial registration. ClincalTrials.gov identifier: http://www.clinicaltrials.gov/ct2/show/NCT00280033?term=NCT00280033&rank=1NCT00280033.